THE INFLUENCE OF ROLE PLAY TECHNIQUE AND LEARNING MOTIVATION TOWARDS THE TENTH GRADE STUDENTS’ SPEAKING ABILITY - Nuraini Nuraini (Esteem Journal of English Education Study Programme, 2022)
The purpose of this research is to find out the influence of role play technique and learning motivation towards the tenth grade students’ speaking ability at Mandiri vocational school of Palembang. To know students’ speaking ability in this study, students were assessed by oral test. The test was analyzed by using descriptive statistic, normality, homogeneity, pair sampled t-test, independent sample t-test and two way ANOVA. Based on the result on two way ANOVA by SPSS 22, the result showed that there was significant influence of role play towards the tenth grade students’ speaking ability, there was significant influence of using role play and conventional teaching technique towards the tenth grade students’ speaking ability between students who have high and low learning motivation at Mandiri Vocational school, there was interaction effect of role play and learning motivation towards the tenth grade students’ speaking ability. It can be concluded that role play technique was quite effective to improve students speaking achievement.